2007
DOI: 10.1007/s10047-007-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with Smart Care after off-pump coronary artery bypass for early extubation

Abstract: The purpose of this study was to compare the intubation time using Smart Care, a knowledge-based system for automated weaning, with that of conventional physician-controlled weaning after off-pump coronary artery bypass (OPCAB) and to determine the efficacy of Smart Care. During 2004, 53 sequential patients were scheduled for isolated coronary artery bypass grafting without cardiopulmonary bypass. Patients were divided into two groups: the Smart Care group (n = 10) and the control group (n = 35). Eight patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In Kataoka's and Naritaka's study (12,14) the authors found no side effects either. These findings were probably due to the frequent observations of SmartCare and the great experience of the physicians during and after the weaning process.…”
Section: Dþscussþonmentioning
confidence: 88%
See 1 more Smart Citation
“…In Kataoka's and Naritaka's study (12,14) the authors found no side effects either. These findings were probably due to the frequent observations of SmartCare and the great experience of the physicians during and after the weaning process.…”
Section: Dþscussþonmentioning
confidence: 88%
“…SmartCare™ (SC) (Drager Medical, Lubeck, Germany) is a automated system, specifically designed to guide weaning and has been associated with a substantial reduction in the duration of ventilation. (9)(10)(11)(12)(13)(14) The aim of the study was to compare the extubation times of protocolized versus www.signavitae.com automated weaning from mechanical ventilation in patients after major surgery in the intensive care unit.…”
Section: Introductþonmentioning
confidence: 99%
“…The SC was recently introduced to Japan, where its efficacy has sporadically been reported in the fields of both cardiovascular surgery and the intensive care unit [9][10] . The present study was performed to examine the efficacy of SC for weaning from the ventilator during postoperative respiratory management in patients surgically treated for esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…After spontaneous breathing was confirmed, weaning was performed using the Smart Care function, which automatically determines the appropriate level of ventilator support. 13 This ventilation management strategy was used in both groups.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%